Are dipeptidyl peptidase-4 inhibitors effective and safe in long term when added to ongoing therapies of diabetics? a real-life study in tertiary referral center - Avci, Deniz; Cetinkaya, Ali (International Journal of Advances in Medicine, 2019)
Background: The aim of this study was to determine how HbA1c, lipid, renal functions and such parameters were affected in the long term by adding dipeptidyl peptidase-4 inhibitors to the ongoing treatment regimens of patients with Type 2 diabetes mellitus. Methods: The study was conducted in diabetes mellitus outpatient clinic of Kayseri Training and Research Hospital between February 2012 and May 2017, with patients who did not achieve the sufficient success in diabetes their controls at the time of admission. From these patients, those who added (dipeptidyl peptidase-4 inhibitors) to their treatments were selected. Patients were followed up as long as they continued to these new treatments and the parameters at the baseline were compared with final values. Results: A total of 80 diabetic patients were followed in the study. The median age of the patients was 56.08±9.71 years. During this follow-up, an average decrease of 1.03% was noted when patients were compared with 9.53±1.87% of the initial hemoglobin A1c, and 8.50±1.48% of the Hemoglobin A1c values at the end of follow-up. This decrease was statistically significant (p <0.001). However, differences in the initial and final values of the lipid parameters of the patients were not statistically significant. Conclusions: Addition of dipeptidyl peptidase-4 inhibitors to patients' treatments causes significant decreases in Hemoglobin A1c mean values. This decline is long lasting. However, there are no positive or negative effects on biochemical parameters such as lipids, kidney and liver functions.